Introduction of the octogon-based consumer warning system and consumption of excessive processed food in nutrients - Alférez Murias, Muriel (2020)
The research aimed to determine potential effects on the introduction of the “octagon” based consumer warning system on the consumption of processed foods that are excessive in nutrients. The research is non-experimental and cross-sectional. The survey was used as a technique, applying a questionnaire to the population aged 15 to 64 from the five most populated districts of the province of Tacna: Colonel Gregorio Albarracín, Tacna, Alto de la Alianza , Ciudad Nueva and Pocollay. For the processing and data analysts the procedure of "Cross Tables" and "Chi - Square" was applied. The results indicate that "Breads and baked goods" are the excessive nutrients that the Tacna population consumes the most. Most of the respondents are unaware of the Law for the Promotion of Healthy Food for Boys, Girls and Adolescents No. 30021, so a high percentage of this ensures that it will generate a positive impact on the population, being in "Total agreement" regarding to the use of octagonal labels and better understanding of octagon labeling. It is concluded that the octagon-based consumer warning system generates effects, both positive and negative, on the consumption habits of processed foods excessive in critical nutrients.